Physical functioning following spinal cord stimulation: a systematic review and meta-analysis. Issue 6 (20th April 2023) - ElSaban, Mariam; Kleppel, Donald J; Kubrova, Eva; Martinez Alvarez, Gabriel A; Hussain, Nasir; D'Souza, Ryan S
Abstract : Background: Spinal cord stimulation (SCS) has emerged as an important treatment for chronic pain disorders. While there is evidence supporting improvement in pain intensity with SCS therapy, efforts to synthesize the evidence on physical functioning are lacking. Objective: The primary objective of this meta-analysis was to assess long-term physical function following 12 months of SCS for chronic back pain. Evidence review: PubMed, EMBASE, Scopus, and CENTRAL databases were searched for original peer-reviewed publications investigating physical function following SCS. The primary outcome was physical function at 12 months following SCS therapy for chronic back pain compared with baseline. A random effects model with an inverse variable method was used. The Grading of Recommendation, Assessment, Development, and Evaluation (GRADE) framework was used to determine the certainty of evidence. Findings: A total of 518 studies were screened, of which 36 were included. Twenty-two studies were pooled in the meta-analysis. There was a significant reduction in Oswestry Disability Index (ODI) scores at all time frames up to 24 months following implantation. Pooled results revealed significant improvement in ODI scores at 12 months with a mean difference of −17.00% (95% CI −23.07 to −10.94, p<0.001). There was a very low certainty of evidence in this finding as per the GRADE framework. There was no significant difference in subgroup analyses based on study design (randomised controlled trials (RCTs) vs non-RCTs), study funding, or stimulation type. Conclusion: This meta-analysis highlights significant improvements in physical function after SCS therapy. However, this finding was limited by a very low GRADE certainty of evidence and high heterogeneity.